Performance of pineapple leaf fibre as reinforcement in oil palm shell lightweight concrete - Tang, Mun Lin (2019)
Concrete is formed by coarse aggregate embedded in the cement matrix which fills the spaces and voids among the aggregate’s particles and glue them together. In this experiment, lightweight concrete, which is more environmentally sustainable as compared to conventional concrete, which fully using cement was studied. Lightweight concrete is more environmentally sustainable as compared to conventional concrete because lightweight concrete reduces usage of cement as well as quantities of aggregates which results in destruction of hills causing geological and environmental imbalance. Conventional concrete is relatively a brittle material where the structural cracks will be developed even before loadings are applied due to its low tensile strength, limited ductility, and little resistance towards cracking. The external load will lead to further propagation of existing cracks and eventually caused spalling of concrete and the newly formed additional cracks. Hence, inclusion of reinforcement in concrete is necessary. Fibres are commonly used in concrete to control the propagation of micro cracks, shrinkage and to improve the strength and performance of concrete. In the past researches, due to consideration of threat to the environment, eco-friendly fibre is introduced to the field of concrete as an alternative source of fibre to be used in concrete for increasing its mechanical properties. The highlight of this research is to focus on the mechanical behaviour of pineapple leaf fibre (PALF) in oil palm shell lightweight concrete in different fibre volume fractions to concrete volume 0.5%, 1.0%, 1.5% and 2.0% of PALF compared to plain concrete. PALF was extracted and then treated with sodium hydroxide with concentration of 10% to enhance fibres durability. In this research, the length of PALF was made constant as 40 mm based on optimum fibre length from previous investigations. The experimental testing in this work include slump test, cube test, four-point bending test and splitting tensile test which comprises of 60 cubes, 15 beams and 15 cylinders. The concrete cubes were tested at the curing age of 3, 7, 14 and 28 days, whereas for cylinder and beam were tested at 28 days. Continuous water curing process was conducted for all cubes, cylinders and beams samples for the required period. From the various test results, the performance of plain concrete and lightweight concrete and mechanical properties of fibre reinforced oil palm shell lightweight concrete were evaluated. The research showed that the compressive strength decreased at all ages with an increase in PALF volume fraction, whereas splitting tensile strength and flexural strength give positive result those with a small amount of fibre addition. The inclusion of PALF increase the tensile and flexural strength up to 3.28 MPa and 6.55 MPa respectively. Compared to the control mix 0%, when the fibre increase to 1.0%, the flexural strength and tensile strength increase up to 36.32%. From the results obtained, 1.0% PALF is the optimum fibre volume ratio for tensile and flexural strength development. In terms of workability, the addition of PALF in concrete mix drastically decreased the workability of freshly mixed concrete as the fibre absorbed water greatly. Hence, it can be concluded that PALF is suitable to be used in lightweight concrete, however not suitable to produce high strength lightweight concrete.